PENGARUH CELEBRITY ENDORSER, BRAND IMAGE, DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA NMAX DI CV. TJAHAJA BARU SURANTIH - Lidya Martha; Dinet Maini (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine the effect of celebrity endorser, brand image, and brand trust on purchasing decisions for Yamaha Nmax motorcycles at CV. Tjahaja Baru Surantih. This research is a quantitative research, the sampling method using purposive sampling technique with the number of respondents 53 people. The data analysis technique used in this study was multiple regression analysis. The results of this study indicate that celebrity endorser has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, and brand trust has a positive and significant effect on purchasing decisions